Transient and steady state dynamic analysis of passive and semi-active suspension systems using half-car model - Faris, Waleed Fekry; Ihsan, Sany Izan; Ahmadian, Mehdi (Inderscience Publishers, 2009)
Several control policies of semi-active system, namely skyhook, groundhook and hybrid controls are presented using a half-car model, as a continuation of the previous work on quarter-car model. Their ride comfort, suspension displacement and road-holding performances are analysed and compared with passive system. The analysis covers both transient and steady state responses in time domain and transfer function in frequency domain. The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement for typical passenger cars. The hybrid control policy is also shown to be a better compromise between comfort, road-holding and suspension displacement than the skyhook and groundhook control policies.